Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D’Agaro, Pierlanfranco (Journal of Clinical Virology, 2015)
[Display omitted] •A rare case of persistent TBEV infection of an immune-suppressed patient.•Virus detection in the erythrocyte fraction is observed for the first time with TBEV.•Shedding of TBEV in the urine lasted for over two months.•Identification of a cluster of three TBEV infected patients in a new area of North-Eastern Italy. A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.